Materials Characterization Techniques: Applications and Features - dos Santos, William Jeremias (Scientia Plena, 2011)
After the second half of the twentieth century there was a great growth in the understanding of the microstructure of materials, and it was only possible through the discovery of new techniques for characterization of materials. Today there is a number of direct and indirect techniques to characterize samples such as x-ray diffraction, atomic absorption, thermal analysis, electron microscopy and heating. This article presents the characteristics of these techniques, the types, extent and applications.